Understanding the Relationship Between Religiousness, Spirituality, and Underage Drinking: The Role of Positive Alcohol Expectancies - Sauer-Zavala, Shannon (Journal of religion and health, 2014)
Research has consistently found that religiousness and spirituality are negatively associated with underage drinking. However, there is a paucity of research exploring the mechanisms by which these variables influence this important outcome. With 344 underage young adults (ages 18-20; 61 % women), we investigated positive alcohol expectancies as a mediator between religiousness and spirituality (measured separately) and underage alcohol use. Participants completed the Religious Commitment Inventory-10, Daily Spiritual Experiences Scale, Alcohol Expectancies Questionnaire, and Drinking Styles Questionnaire. Results indicate less positive alcohol expectancies partially mediate the relationship between both religiousness and spirituality and underage alcohol use. This suggests religiousness and spirituality's protective influence on underage drinking is partly due to their influence on expectations about alcohol's positive effects. Since underage drinking predicts problem drinking later in life and places one at risk for serious physical and mental health problems, it is important to identify specific points of intervention, including expectations about alcohol that rise from religious and spiritual factors.